2015
DOI: 10.3892/ol.2015.3730
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA-PKcs enhances radiosensitivity and increases the levels of ATM and ATR in NSCLC cells exposed to carbon ion irradiation

Abstract: Non-small cell lung cancer (NSCLC) exhibits radioresistance to conventional rays, due to its DNA damage repair systems. NSCLC may potentially be sensitized to radiation treatment by reducing those factors that continuously enhance the repair of damaged DNA. In the present study, normal lung fibroblast MRC-5 and lung cancer A549 cells were treated with NU7026 and CGK733, which are inhibitors of the DNA-dependent protein kinase catalytic subunit (PKcs) and ataxia telangiectasia mutated (ATM) and ataxia telangiec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Several lines of evidence have demonstrated that DNA repair mechanisms are employed by cancer cells to resist ionizing radiation, resulting in cancer recurrence and final radiotherapy failure ( 4 6 ). It has been reported that the protein kinases, ataxia telangiectasia mutated (ATM) and ATM and Rad3 related (ATR), are major regulators in the DNA damage response to radiation ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have demonstrated that DNA repair mechanisms are employed by cancer cells to resist ionizing radiation, resulting in cancer recurrence and final radiotherapy failure ( 4 6 ). It has been reported that the protein kinases, ataxia telangiectasia mutated (ATM) and ATM and Rad3 related (ATR), are major regulators in the DNA damage response to radiation ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Several kinase inhibitors such as wee1 kinase inhibitor AZD1775, inhibitor of DNA-PKcs kinase and ATR inhibitor were proven to enhance the radiosensitivity of human cancers. [17][18][19] In our study, by screening of 93 kinase inhibitors, we found NVP-BSK805, a specific inhibitor of JAK2 kinase, 20 significantly improved the radiosensitivity of esophageal cancer cells in vitro and in vivo. As found in other models, 21 JAK2 inhibition by NVP-BSK805 efficiently blocked the phosphorylation of STAT5.…”
Section: Discussionmentioning
confidence: 66%
“…A large number of studies have shown that apoptosis is important in tumor radiotherapy ( 30 , 31 ). Therefore, the present study further tested whether FlaA N/C affects cell apoptosis after radiation.…”
Section: Resultsmentioning
confidence: 99%